2009
DOI: 10.1111/j.1365-2621.2009.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of a stimulant coconut water–acerola fruit juice beverage

Abstract: The objective of this work was to study the stability of a beverage formulated with acerola fruit juice and green coconut water with added caffeine. The beverage was prepared with 25% acerola pulp, 75% green coconut water and sugar up to 12°Brix, and caffeine (125 mg L )1 ), heat processed at 90°C for 30 s and packed in 250-mL glass bottles. Chemical, physicochemical, microbiological and sensory analyses of the beverage were performed just after processing and during 6 months of storage at room temperature (27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In the determination of ascorbic acid, only potassium sorbate showed a significant response, and the lower the concentration of potassium sorbate, the greater the degradation of ascorbic acid, as seen in Figure 1e. Lima et al (2009) also found a decrease in ascorbic acid concentration in coconut water-acerola fruit juice supplemented with caffeine, at a rate of 1.24 mg.100 mL -1 .day -1 .…”
Section: Resultsmentioning
confidence: 78%
“…In the determination of ascorbic acid, only potassium sorbate showed a significant response, and the lower the concentration of potassium sorbate, the greater the degradation of ascorbic acid, as seen in Figure 1e. Lima et al (2009) also found a decrease in ascorbic acid concentration in coconut water-acerola fruit juice supplemented with caffeine, at a rate of 1.24 mg.100 mL -1 .day -1 .…”
Section: Resultsmentioning
confidence: 78%
“…The color changes that occur during storage in orange juice with addition of RPO-NLC may be caused by non-enzymatic browning reactions. Non-enzymatic browning reactions result from several reactions such as the maillard reaction, caramelization process, ascorbic acid browning and pigment degradation (Da S. Lima et al, 2009). Chauhan et al (2014) reported that there was color change in lemon juice mixed with coconut water, the change was caused by a nonenzymatic browning reaction during storage.…”
Section: Research Articlementioning
confidence: 99%
“…The weight of the protein sediment was measured to 2 decimal places using a weighing machine (PA4102, OHAUS, USA). The weights of the sludge obtained from each condition were compared based on the flow rate; the coconut meat water was sterilized using an autoclave (HA-300MIV, Hirayam, Japan) at 121°C for 15 min (Chiewchan et al, 2006) followed by storage of the sterilized product at 27 ± 2°C in transparent glass bottles packaged in room and kept away from light (Lima et al, 2009).…”
Section: Determining Optimum Flow Rate Of Milk Cream Electric Centrifugal Separator To Separate Residual Protein Sludgementioning
confidence: 99%